Upaya Meningkatkan Minat dan Hasil Belajar PPKn Menggunakan Metode Teka-Teki Silang di Kelas VIII D SMP Negeri 1 Ende - Emmy Rumbaya (Ekspektasi: Jurnal Pendidikan Ekonomi, 2023)
This study aims to determine the increase in student interest and learning outcomes after applying the Crossword Puzzle method to Civics learning in class VIII D of SMP Negeri 1 Ende. The research method used is classroom action research by going through the three stages of the cycle. In cycle II it still failed to achieve the predetermined success criteria of 75% even though there was an increase in the percentage from cycle I. This was evidenced by the average percentage of indicators of student interest in learning which increased by 8% from cycle I to 70%. The increase in the percentage of interest indicators also affected the increase in the percentage of student learning outcomes indicators which increased by 40% from cycle I to 60% even though the results were still below the established success criteria of 75%. In cycle III, students' interest in learning increased from cycle II by 18% to 88%. The application of the Crossword Puzzle learning method can improve student learning outcomes. This is evidenced by the percentage of students who achieved KKM scores in cycle I by 20% increasing to 60% in cycle II. Furthermore, it still increased to 80% in cycle III.